The Dual Edge of Backdoors: Accuracy Analysis and Preventive Strategies for Secure Systems - Gupta, Arushi; Tanweer, Safdar; Khalid, Syed Sibtain; Rao, Naseem (International Journal of Computer Sciences and Engineering, 2025)
While digital transformation's benefits are reciprocal, we have vulnerabilities with rapid technological developments, one of which is malware, one of the biggest dangers to digital security. It’s harmful software that can mess up, damage, or sneak into computer systems without permission. In this article, we are going to use Kali Linux backdoor attacks, as we know that backdoor vulnerabilities have emerged as a critical threat to cybersecurity, with recent reports indicating a 45% increase in backdoor-related incidents over the past year. Hence, with the availability of free online tools like VirusTotal and Hybrid analysis, detection remains challenging, but it can detect up to an average detection rate of only 72% for sophisticated backdoors. As such, backdoors are covert methods for attackers to access systems that bypass typical security barriers and represent a major weakness to the integrity, confidentiality, and availability of information systems. This paper defines the implementation of a backdoor and analyzes existing mitigation techniques. It also introduces a holistic approach that combines anomaly detection and code analysis on how we implemented this backdoor using two operating systems. It covers methodologies for monitoring insider activities, detecting anomalous behavior (with the help of free tools) that may indicate the presence of backdoors, and protective actions to reduce the threat posed by trusted users. In this paper, we focus on insiders and their backdoor exploitation capabilities, discussing real-world scenarios in which insiders exploited backdoors for data exfiltration, sabotage, or espionage.